Determinants of Male and Female Infertility: A Systematic Review - Dewi Puspitaningrum; SA Nugraheni (Universitas Muhammadiyah Semarang, 2022)
Infertility is a problem that is still a lot in the world. Infertility cases are fertility disorders in both women and men caused by reproductive disorders and environmental factors. The purpose of this study was to determine the determinants of infertility by using studies obtained from 8 national and international databases, namely Garuda portal national system, Google Scholar and Sinta, international system with Science Direct, Scopus, Cambridge Core, Proquest, Springer Link. Then processed and selected with a prism diagram. The relevant results are 10 studies through the national system and 10 studies through the international system. It was found that there are 4 categories that are the determinants of male and female infertility, including the history of reproductive disorders, prevention in infertility, Problem Solving the mental readiness of the couple and the lifestyle of the couple.